Simulation of dynamic processes in hydraulic accumulators - Mamčic, Stanislav; Bogdevičius, Marijonas (Transport, 2010)
The article focuses on pressure pulsations in hydraulic systems, the means reducing them and examines the structure of hydraulic accumulators, including their features and differences. Using the method of characteristics and Fortran software, a dynamic model of a hydraulic system is created. By changing the content of a hydraulic accumulator, the paper analyzes the amplitude of pressure waves, the distance between hydraulic accumulators and the dependency of the pulsations of pressure waves on the aforementioned sizes. First published online: 27 Oct 2010